2022
DOI: 10.5802/crgeos.97
|View full text |Cite
|
Sign up to set email alerts
|

Peralkaline silicic extrusive rocks: magma genesis, evolution, plumbing systems and eruption

Abstract: Peralkaline silicic extrusive rocks are an important component of the volcanological record.Here we review several aspects of their formation and evolution, including the tectonic settings in which they occur, their main petrological and geochemical features, the magmatic lineages along which they evolve, and the parameters (T , P , f O 2 , melt water contents) that control the lineages. Particular attention is paid to the composition of the extraordinary melts formed at the lowest temperatures. Various lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 254 publications
0
3
0
Order By: Relevance
“…The differentiated products of the Velay are represented by trachytes and phonolites with alkalinity (Na / Al-K) ranging from 0.8 to 1.3 (Fig. 2b, c;Batard, 1974;Macdonald et al, 2021, for another recent review). Batard (1974) showed that phonolites are derived from a normal crystallization sequence at depth (magnetite, ilmenite, apatite, zircon, sphene, pyroxene, plagioclase, amphibole, alkali feldspar, feldspathoid) that was superimposed by reverse paragenesis (feldspathoid, alkali feldspar, Zr/Ti silicates, alkali pyroxene) developed at lower depth.…”
Section: The Velay Volcanismmentioning
confidence: 99%
“…The differentiated products of the Velay are represented by trachytes and phonolites with alkalinity (Na / Al-K) ranging from 0.8 to 1.3 (Fig. 2b, c;Batard, 1974;Macdonald et al, 2021, for another recent review). Batard (1974) showed that phonolites are derived from a normal crystallization sequence at depth (magnetite, ilmenite, apatite, zircon, sphene, pyroxene, plagioclase, amphibole, alkali feldspar, feldspathoid) that was superimposed by reverse paragenesis (feldspathoid, alkali feldspar, Zr/Ti silicates, alkali pyroxene) developed at lower depth.…”
Section: The Velay Volcanismmentioning
confidence: 99%
“…Comendites are dominantly produced by crystal fractionation of alkali basalt, via a trachyte stage (Macdonald et al, 2008;2021). The 10-30 km 3 of near aphyric comendite discharged with the Millennium Eruption implies efficient separation from a trachytic magma mush at depth, whose volume should be approximately 50-100 km 3 , on the basis of the fivefold increase in incompatible elements between trachyte and rhyolite (Fig.…”
Section: The Case For Chlorinementioning
confidence: 99%
“…Journal Pre-proof Carlo et al, 2010;Lucic et al, 2016;Romano et al, 2018;Iddon and Edmonds, 2020), with pre-eruptive H 2 O content of 3-5 wt%, very little if any CO 2 (hence XH 2 O fluid =1), at pressures of 1-3 kb, ie occupying a position similar to those of arc-magmas. This reflects the overall incompatible behaviour of H 2 O in crystallising magmas, and the extreme degree of fractionation of parental magmas that felsic daugthers produced in ridges or hot-spot contexts require (e.g., Macdonald et al, 2021). Anyway, the very CO 2 -rich nature of high pressure fluids in ridges and hot spot settings indicates that underplating of magmas in the crust of such settings will likely favour crystallization rather than melting.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%